Ergonomic Analysis of Working Postures at a Construction Site Using Rula and Reba Method (Journal of Engineering Science, 2023)
Musculoskeletal Disorders (MSDs) are the main work-related problems in construction sites around the world. Awkward working posture is mainly responsible for occupational musculoskeletal injuries. The main objectives of the research were to analyse the working postures of construction workers and assess the level of risk of injury in their work. Four categories of working postures were collected from elementary works as a form of still pictures from the construction site. Two assessment tools RULA (Rapid Upper Limb Assessment) & REBA (Rapid Entire Body Assessment) were used to assess the working postures of construction workers. Results showed that Beam and column casting and masonry workers were at high risk of injury due to the absence of maintaining proper working postures during the work. This study suggested to construction workers to maintain proper postures during works for avoiding any occupational injuries.Journal of Engineering Science 14(1), 2023, 43-52